Bidirectional regulation of fragile X mental retardation protein phosphorylation controls rhodopsin homoeostasis. (31st October 2016) - Wang, Xiao; Mu, Yawen; Sun, Mengshi; Han, Junhai
Abstract: Homoeostatic regulation of the light sensor, rhodopsin, is critical for the maintenance of light sensitivity and survival of photoreceptors. The major fly rhodopsin, Rh1, undergoes light-induced endocytosis and degradation, but its protein and mRNA levels remain constant during light/dark cycles. It is not clear how translation of Rh1 is regulated. Here, we show that adult photoreceptors maintain a constant, abundant quantity of ninaE mRNA, which encodes Rh1. We demonstrate that the Fmr1 protein associates with ninaE mRNA and represses its translation. Further, light exposure triggers a calcium-dependent dephosphorylation of Fmr1, which relieves suppression of Rh1 translation. We demonstrate that Mts, the catalytic subunit of protein phosphatase 2A (PP2A), mediates light-induced Fmr1 dephosphorylation in a regulatory B subunit of PP2A (CKa)-dependent manner. Finally, we show that blocking light-induced Rh1 translation results in reduced light sensitivity. Our results reveal the molecular mechanism of Rh1 homoeostasis and physiological consequence of Rh1 dysregulation.